A CONTRASTIVE ANALYSIS BETWEEN ENGLISH AND INDONESIAN COPULATIVE VERBS - Sulaiman, Masagus; Syahri, Indawan; Saputri, Kurnia (Universitas Muhammadiyah Palembang, 2022)
This research aims at determining the similarities, dissimilarities, and possible learning difficulties faced by the students learning English and Indonesian copulative verbs, as well as the recommendations to TEFL. The descriptive research design was used. The documentation technique was applied to collect the data. To analyze the data, the researchers used a descriptive analysis. The results showed that there were two similarities between English and Indonesian copulative verbs in meanings and dynamic verb. The three dissimilarities were in grammatical structure, tense on subject-verb agreement and certain verbs. The possible learning difficulties faced by the students learning English and Indonesian copulative verbs was tense and subject-verb agreement. The recommendations of this research was as a fundamental teaching guidance in helping English teachers design a better teaching Grammar on copulative verbs, in terms of nonverbal copulative nominal, stative copulative nominal and dynamic copulative nominal.